The Stability of Protein Therapeutics: A Significant Challenge in the Formulation of Biopharmaceuticals - Nuwarda, Rina Fajri; Ramadhania, Zelika Mega; Novianti, Mia Tria (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Protein-based therapies have already brought about a significant transformation in the field of medicine, and their use continues to grow. The development of protein therapeutics has revolutionized the treatment of various diseases, such as cancer, autoimmune disorders, viral infections, cardiovascular disease, myocardial infarction, etc. Consequently, it is crucial to ensure the stability of formulations, given their rapid growth. Preserving the structural integrity of protein-based medicines is a significant challenge in developing a stable and high-quality formulation. This challenge arises during various stages, including manufacturing procedures, storage, handling, distribution, and delivery due to proteins' intricate and delicate nature. Hence, it is crucial to thoroughly understand the various degradation mechanisms that impact protein stability to enhance different variables and minimize the formation of degradation products, such as aggregation, oxidation, deamidation, etc., which could potentially have clinical implications. This review provides an important step in understanding the process of protein degradation and offers a beneficial approach to investigate the degradation of proteins, specifically aggregation, through several analytical and biophysical methods. This is important for facilitating the further advancement of protein-based therapies.